Analyzing and Identifying the Factors Affecting the Global Supply Chain Competitiveness of Industrial Products - Aleksandr P. Latkin; Yuliia P. Maidanevych; Pavel I. Komarov (International Journal of Supply Chain Management, 2018)
Technological progress is one of the main factors driving long-run economic growth, whether referred to some enterprises that need progress and advancement or to the national economy in general. Innovations make the production process more efficient, thereby affecting its competitive ability. Switching from an economic system that takes considerable time and labor to a technology-intensive one is what drives economic modernization. Industrial production plays a key role in shaping the competitiveness of national economy. Competitiveness index is one of the most important indicators. The purpose of this research is to analyze and identify the most significant factors affecting the global supply chain competitiveness of industrial products. The tie between them was established through the coefficient of correlation between the global manufacturing competitiveness index and the index of performance in the Russian manufacturing sector. The strongest correlation was found between the global manufacturing competitiveness index and the industrial production index, high-technology exports and RD expenditure.